2021
DOI: 10.1002/cphc.202100679
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Intersystem Crossing of Single Deuterated Perylene Molecules in a Dibenzothiophene Matrix

Abstract: Intersystem crossing to the long‐lived metastable triplet state is often a strong limitation on fluorescence brightness of single molecules, particularly for perylene in various matrices. In this paper, we report on a strong excitation‐induced reverse intersystem crossing (rISC), a process where single perylene molecules in a dibenzothiophene matrix recover faster from the triplet state, turning into bright emitters at saturated excitation powers. With a detailed study of single‐molecule fluorescence autocorre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Moradi et al investigated a new guest–host system, DBT in DBN discussed earlier, which demonstrated a strong linear Stark effect . Smit et al recently reported the reverse intersystem crossing (rISC) of deuterated perylene in dibenzothiophene, which helped in recovering the fluorescence loss by the ISC process. Such a mechanism is promising for controlling the triplet state lifetime, specifically for the purpose of super-resolution imaging under cryogenic conditions. , Apart from investigating the electronic states of a molecule, the study of a vibrational energy state and its higher-resolution spectroscopic investigation are important steps for quantum-optical applications.…”
Section: Past and Recent Developments In Cryogenic Single-molecule Fl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moradi et al investigated a new guest–host system, DBT in DBN discussed earlier, which demonstrated a strong linear Stark effect . Smit et al recently reported the reverse intersystem crossing (rISC) of deuterated perylene in dibenzothiophene, which helped in recovering the fluorescence loss by the ISC process. Such a mechanism is promising for controlling the triplet state lifetime, specifically for the purpose of super-resolution imaging under cryogenic conditions. , Apart from investigating the electronic states of a molecule, the study of a vibrational energy state and its higher-resolution spectroscopic investigation are important steps for quantum-optical applications.…”
Section: Past and Recent Developments In Cryogenic Single-molecule Fl...mentioning
confidence: 99%
“…Therefore, the molecules have to be excited by the S 0 → S 1 transition, which for perylene has a wavelength between 440 and 450 nm. Once in the excited state, a small fraction of the excitations are converted to the triplet excited state, , with a typical yield of about 10 –6 . The radiative quantum yield of the triplet would be expected to be around 10 –2 –10 –3 , thus reducing the yield of phosphorescence photons to 10 –8 –10 –9 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The former is the one that served to establish room-temperature triplet state characteristics; the latter has recently been proposed as a suitable candidate for cryoactivation-based microscopy . Both prototypical FPs serve as benchmarks for the performance characterization of a steady stream of newly developed FPs of various colors and enhanced properties. , Here, we provide insight into two processes that decisively determine the performances of EGFP and rsEGFP2: light-induced formation and decay of the first excited triplet state T 1 (forward and reverse intersystem crossing, denoted FISC and RISC, respectively). Strategies to enhance photostability by RISC enhancement have been proposed . In EGFP, T 1 has been shown to live few milliseconds at room temperature (RT), and a T 1 absorption spectrum at RT has been measured, but the dominant contribution of ground-state bleaching prevented the determination of the T 1 absorption coefficient at the popular excitation wavelength 488 nm .…”
Section: Introductionmentioning
confidence: 96%
“…18−21 Strategies to enhance photostability by RISC enhancement have been proposed. 20 In EGFP, T 1 has been shown to live few milliseconds at room temperature (RT), and a T 1 absorption spectrum at RT has been measured, 11 but the dominant contribution of ground-state bleaching prevented the determination of the T 1 absorption coefficient at the popular excitation wavelength 488 nm. 11 Here, we make use of the cooling-induced lifetime prolongation of T 1 to measure its complete NUV−vis−NIR absorption spectrum at CT, immediately after a saturating pulse of 488 nm laser excitation.…”
Section: ■ Introductionmentioning
confidence: 99%